Ionic liquid as a potential solvent for preparation of collagen-alginate-hydroxyapatite beads as bone filler - Iqbal, B. (Taylor and Francis Inc., 2018)
In this study, collagen/alginate/hydroxyapatite beads having different proportions were prepared as bone fillers for the restoration of osteological defects. Ionic liquid was used to dissolve the collagen and subsequently the solution was mixed with sodium alginate solution. Hydroxyapatite was added in different proportions, with the rationale to enhance mechanical as well as biological properties. The prepared solutions were given characteristic bead shapes by dropwise addition into calcium chloride solution. The prepared beads were characterized using FTIR, XRD, TGA and SEM analysis. Microhardness testing was used to evaluate the mechanical properties. The prepared beads were investigated for water adsorption behavior to ascertain its ability for body fluid uptake and adjusted accordingly to the bone cavity. Drug loading and subsequently the antibacterial activity was investigated for the prepared beads. The biocompatibility was assessed using the hemolysis testing and cell proliferation assay. The prepared collagen-alginate-HA beads, having biocompatibility and good mechanical properties, have showed an option of promising biologically active bone fillers for bone regeneration. Â© 2018 Informa UK Limited, trading as Taylor & Francis Group.